2006
DOI: 10.1017/s0022215106002362
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic sudden sensorineural hearing loss: prognostic factors

Abstract: The present study revealed that there are certain factors that affect prognosis in idiopathic SSHL. This is very important in counselling patients and may affect current clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
62
5
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 7 publications
9
62
5
2
Order By: Relevance
“…If the 10 patients within 2 weeks from the onset were excluded to eliminate the effect from nature spontaneous recovery, 43.5% patients (27/62) showed clear or partial improvement. These results were similar to or higher than average recovery rate of other studies especially considering the time interval from onset of ISSHL to start treatment ( Xenellis J et al, 2006;Haynes DS et al, 2007;Raymundo IT et al, 2010;Wu HP et al, 2011;Rauch SD et al, 2011;Park MK et al, 2011).…”
Section: Fig 3 Decision Tree Model Of Important Variables As Prognosupporting
confidence: 89%
See 3 more Smart Citations
“…If the 10 patients within 2 weeks from the onset were excluded to eliminate the effect from nature spontaneous recovery, 43.5% patients (27/62) showed clear or partial improvement. These results were similar to or higher than average recovery rate of other studies especially considering the time interval from onset of ISSHL to start treatment ( Xenellis J et al, 2006;Haynes DS et al, 2007;Raymundo IT et al, 2010;Wu HP et al, 2011;Rauch SD et al, 2011;Park MK et al, 2011).…”
Section: Fig 3 Decision Tree Model Of Important Variables As Prognosupporting
confidence: 89%
“…have been suggested. Some studies have reported that the female gender was suggested to be poor prognostic factor for recovery of hearing loss (Ceylan et al, 2007) and male gender was related to better hearing outcomes (Xenellis J et al, 2006). In our study, correlation between gender and prognosis for recovery of hearing loss was not evident.…”
Section: Fig 3 Decision Tree Model Of Important Variables As Prognocontrasting
confidence: 68%
See 2 more Smart Citations
“…Increasing age was found to be associated with poorer prognosis in most of the studies. 2,10,11 However, in a retrospective study which was conducted to find out the factors that affect hearing outcome, the result indicated that age of the patient had no effect on the outcome of hearing.…”
Section: Discussionmentioning
confidence: 99%